PELAKSANAAN INTERAKSI EDUKATIF DALAM PEMBELAJARAN EKONOMI KELAS X PIPS 2 SMA NEGERI 2 PONTIANAK - Dina Fransiska; Junaidi H Matsum; Khosmas Khosmas (Universitas Tanjungpura, 2019)
AbstractThe study was aimed to determine the implementation of educational interaction in learning economy subject X PIPS 2 SMA Negeri 2 Pontianak.1) Implementation of educational interactions in economic learning class X PIPS 2 SMA Negeri 2 Pontianak; 2) obstacles that occurred in the implementation of educational interactions in learning; 3) as well as efforts that used overcome what happened in educational interactions. This research was used qualitative research methods in a descriptive form. Data collection tools used were observation guides, interview guides, and documentation. The results of this study indicated that; 1) the implementation of educational interactions in economic learning forms one-way communication patterns and two-way communication patterns; 2) the t factor inhibited educational interactions in the economic learning of students who seem less motivated to discuss learning material and students who it not confident to answer complicated questions. The teacher asked the students who looked shy to ask for help from the teacher who helped. talking; 3) Efforts that implemented overcome the challenges in the implementation of educational interactions was the teacher told the story before has explained the learning material and the teacher provided motivation for students to answer questions and not to be shy about asking questions related to the learning material that has been approved. Keywords: educational interaction, Economic learning